Akuntabilitas Administrasi Pemerintahan Dalam Sistem Ppdb Online: Analisis Yuridis Terhadap Dugaan Maladministrasi Pelayanan Pendidikan Di Dinas Pendidikan Kota Gorontalo - Hanasi, Raihan A.; Melikuestri, Endah; Daud, Fidyan; Juliawati, Ni Ketut; Pantoiyo, Alya Putri (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
Online Student Admission (PPDB) is a form of digital transformation in public services within the education sector aimed at improving transparency, effectiveness, efficiency, and accountability in educational service delivery. However, its implementation still faces various challenges that may lead to maladministration, including lack of information transparency, procedural irregularities, system errors, service delays, and alleged discrimination in student selection processes. This study aims to analyze the legal foundations of governmental administrative accountability in the implementation of online PPDB, identify forms of alleged maladministration in educational services, and formulate strategies to strengthen accountability in the implementation of online PPDB at the Gorontalo City Education Office. This research employs a qualitative method with a literature review approach through the examination of laws and regulations, scientific journals, books, previous studies, and relevant policy documents. Data were analyzed using qualitative content analysis techniques. The findings indicate that the accountability of online PPDB implementation has been normatively regulated through various legal frameworks emphasizing transparency, legal certainty, fairness, and public responsibility. Nevertheless, potential maladministration remains due to weak supervision mechanisms, suboptimal information technology systems, and limited public access to information. Therefore, strengthening oversight mechanisms, optimizing digital systems, improving the capacity of public officials, and enhancing public participation are necessary to realize accountable, transparent, and good governance-based educational services.